Palinoestratigrafía de depósitos del Oligoceno tardío-Mioceno, en el área sur del Golfo San Jorge, provincia de Santa Cruz, Argentina - Barreda, Viviana Dora (2000)
A preliminar palynostratigraphic framework is proposed for Cenozoic deposits cropping out in the southern San Jorge Gulf area, Santa Cruz Province, Argentina. Pollen and spores assemblages and associated dinoflagellate cysts recovered from three sections, Mazarredo, Punta Nava and El Faro, were analysed. On the basis of the palynological content two units were recognised and inforrnally named: Unit 1 and Unit 2. Unit 1, represented in Mazarredo and Punta Nava sections, was assigned to the Late Oligocene. The paleoenvironment was identified as a lagoon for the former and inner shelf for the latter. The underlying Unit 2, comprising the top of Punta Nava and El Faro sections, is onsidered to be Early Miocene in age and deposited in a sublitoral to coastal environment. It can be correlated with the Cheuque Formation (Chubut Province). Both dinoflagellate cyst and adjacent land derived pollen and spores suggest humid and warm -temperate climatic conditions for the Late Oligocene and a slight deterioration for the Early Miocene.